2018
DOI: 10.3389/fpsyg.2018.01987
|View full text |Cite
|
Sign up to set email alerts
|

The Multiple Determinants of Maternal Parenting Stress 12 Months After Birth: The Contribution of Antenatal Attachment Style, Adverse Childhood Experiences, and Infant Temperament

Abstract: Parenting stress can influence caregiving behavior negatively, which in turn may harm children’s development. Identifying precursors of parenting stress, preferably beginning during pregnancy and throughout the first year of life, is therefore important. The present study aims to provide novel knowledge on this issue through a detailed examination of the association between maternal attachment style and later parenting stress. Moreover, we examine the role of several additional risk factors, specificially the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
41
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 77 publications
6
41
1
2
Order By: Relevance
“…We also found that paternal symptoms of anxiety and depression during pregnancy as well as their own adverse childhood experiences predicted stress and a negative perception of the infants’ behaviour 55. In a similar vein, we investigated the multiple determinants of mothers’ parenting stress and found that partner attachment style assessed prenatally was a salient predictor of such stress 12 months after birth 18. We further found a link between maternal adverse childhood experiences and later parenting stress, and showed that partner attachment style operated as a mediator in this link.…”
Section: Patient and Public Involvement Statementmentioning
confidence: 83%
See 4 more Smart Citations
“…We also found that paternal symptoms of anxiety and depression during pregnancy as well as their own adverse childhood experiences predicted stress and a negative perception of the infants’ behaviour 55. In a similar vein, we investigated the multiple determinants of mothers’ parenting stress and found that partner attachment style assessed prenatally was a salient predictor of such stress 12 months after birth 18. We further found a link between maternal adverse childhood experiences and later parenting stress, and showed that partner attachment style operated as a mediator in this link.…”
Section: Patient and Public Involvement Statementmentioning
confidence: 83%
“…The most important findings generated by the cohort so far can be summarised in three main domains. The first domain concerns parental mental health functioning in the perinatal period and factors related to parental anxiety, depression and stress in mothers and fathers 18 22 54 55. The second domain is directed towards child functioning and early detection of infants and toddlers at risk,23 51 52 56 while the third domain concerns maternal nutrition during pregnancy and its possible relation to early child development 32 57 58…”
Section: Patient and Public Involvement Statementmentioning
confidence: 99%
See 3 more Smart Citations